2014
DOI: 10.1063/1.4875239
|View full text |Cite
|
Sign up to set email alerts
|

Study of valence-band intersublevel transitions in InAs/GaAs quantum dots-in-well infrared photodetectors

Abstract: The n-type quantum dot (QD) and dots-in-well (DWELL) infrared photodetectors, in general, display bias-dependent multiple-band response as a result of optical transitions between different quantum levels. Here, we present a unique characteristic of the p-type hole response, a wellpreserved spectral profile, due to the much reduced tunneling probability of holes compared to electrons. This feature remains in a DWELL detector, with the dominant transition contributing to the response occurring between the QD gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The dashed lines are the calculated using an effective-mass method. The labeled HH1-HH3 are the levels of the In 0.15 Ga 0.85 As/GaAs QW[13]. Indicated transitions agree with the experimental response.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…The dashed lines are the calculated using an effective-mass method. The labeled HH1-HH3 are the levels of the In 0.15 Ga 0.85 As/GaAs QW[13]. Indicated transitions agree with the experimental response.…”
supporting
confidence: 66%
“…1(a) and (b), respectively [12,13]. The absorbing region consists of 10 periods of InAs QDs, between which is an 80-nm thick undoped GaAs layer.…”
Section: Device Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the demonstrations of QDIPs were achieved with n -type III to V self-assembled nanoheterostuctures. Only limited studies of p -type QDIPs have been reported [ 3 , 4 ]. The attractive features of p -QDIPs include a well-preserved spectral profile [ 3 ], as an opposite to a conventional n -type response strongly dependent on applied bias, increased density of states, and lower dark current due to the higher hole effective mass [ 4 ].…”
Section: Introductionmentioning
confidence: 99%